2021
DOI: 10.3390/microorganisms9050919
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Infection with Hemotropic Mycoplasmas in Free-Ranging Dogs and Wild Foxes Across Six Bioclimatic Regions of Chile

Abstract: Blood samples of 626 rural dogs, 140 Andean foxes (Lycalopex culpaeus), and 83 South American grey foxes (L. griseus) from six bioregions of Chile spanning 3000 km were screened for Mycoplasma DNA by conventional PCR and sequencing. Risk factors of infection were inferred using Generalized Linear Mixed Models and genetic structure by network analyses. Overall, Mycoplasma haemocanis/Mycoplasma haemofelis (Mhc/Mhf) and Candidatus Mycoplasma haematoparvum (CMhp) observed prevalence was 23.8% and 12.8% in dogs, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Interestingly, the prevalence of the two hemoplasma species in the studied dog population differs when co-infections are evaluated. When comparing the prevalence obtained with our specific primers with the screening protocol and direct sequencing alone, as reported by Di Cataldo et al ( 2021b ), prevalence increased from 21% to 28% for Mhc and from 13.5% to 31% for CMhp. The reason for this difference could be due to a lower bacteremia level of CMhp than of Mhc and must be taken into account when studying these pathogens.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, the prevalence of the two hemoplasma species in the studied dog population differs when co-infections are evaluated. When comparing the prevalence obtained with our specific primers with the screening protocol and direct sequencing alone, as reported by Di Cataldo et al ( 2021b ), prevalence increased from 21% to 28% for Mhc and from 13.5% to 31% for CMhp. The reason for this difference could be due to a lower bacteremia level of CMhp than of Mhc and must be taken into account when studying these pathogens.…”
Section: Discussionsupporting
confidence: 75%
“…was screened by conventional PCR (cPCR) with the primers and run protocols previously described (Millán et al 2019 ). The prevalence of three of the pathogens was included in country-wide surveys published elsewhere (Di Cataldo et al 2021a ; Cataldo et al 2021b , 2022 ). Samples scored positive for Mycoplasma were examined with specific primers for Mycoplasma haemocanis (Mhc) and Candidatus Mycoplasma haematoparvum (CMhp) to detect coinfections (Watanabe et al 2008 ; Martínez-Díaz et al 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have successfully transmitted feline hemoplasma infection via subcutaneous inoculation of blood containing low numbers of organisms, suggesting possibility of pathogens transmission by ghting and biting in the eld 35 . Association of infection rate and higher age of dogs is in agreement with the recent studies, which reported hemoplasmas to be more prevalent in older dogs 24,33,36 and could be due to longer exposure time to pathogen. However, we found no signi cant association between hemoplasma infection rate and gender or breed, which is in accordance with previous reports in Cuba 37 , Nigeria 38 , Turkey 29 and Mediterranean countries 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, higher prevalences of canine hemoplasmosis have been reported in countries and regions where R. sanguineus s.l. ticks are found more commonly 33 hypothesizing that this tick may be a possible vector for the transmission of canine hemoplasma species. In contrast, none of 350 individual R. sanguineus ticks collected from dogs in a study in Turkey where brown dog tick is prevalent 34 ; and none of the tick specimens including 204 fully engorged nymphs removed from dogs, and 2100 nymphs and 85 adults collected from the grounds of the same shelter where both pathogens were present in examined dogs suggest that R. sanguineus s.l.…”
Section: Discussionmentioning
confidence: 99%